Probing the IGM with the Lyman-Alpha Forest through Cosmic Time - Nasir, Fahad (2018)
The Lyα forest is a series of absorption lines seen in quasar spectra and is a powerful tool for probing the thermal state of the intergalactic medium (IGM) across a wide redshift range. At intermediate redshifts (2< z <5), the statistical properties of the Lyα forest predicted by recent hydrodynamical simulations are in good agreement with a range of spectroscopic data. However, at lower and higher redshifts this is still not the case. Some of the key questions still challenging our understanding at low redshifts are the nature of absorbers, the evolution of the ultraviolet background and the impact of feedback from supernovae and active galactic nuclei (AGN). Furthermore, as a range of reionsation models remain unconstrained and the precise timing of reionsation remains elusive, high redshift Lyα forest data can provide valuable insight due to its sensitivity to the post-reionsation thermal properties of the IGM. At low redshift, this investigation focuses on understanding the effect of different feed-back prescriptions on the properties of the Lyα forest using simulations from the Sherwood simulation suite. The simulations incorporate three different prescriptions for treating cold dense gas and galactic feedback from supernovae and AGN. These implementations have only a small effect on the properties of the Lyα column density distribution function (CDDF) and Lyα line velocity width distribution. Therefore, feedback does not solve the discrepancy between the Cosmic Origins Spectrograph (COS) observations of the CDDF at z≃0.1 for high column density systems (NHI>1014cm−2), as well as the line width distribution, which has lines broader then the simulation data. Some of the possible solutions may be feedback that ejects more overdense gas into the IGM, an increase in the temperature of the overdense gas (which is rather fine-tunedso that the gas is able to still contribute to the Lyα forest), or an unresolved turbulentin the IGM. The low redshift Lyα forest investigation is concluded by performing a series of numerical convergence tests on the quantities most widely employed in absorption line studies at low redshift. The mass resolution of the simulations can significantly impact on the estimated line velocity widths, by overestimating line widths for low mass resolution runs. By contrast, the Lyα CDDF is quite well converged for low column density absorbers. At higher redshifts, a feasibility analysis to constrain the thermal history of the IGM using cosmological hydrodynamical simulations of the Lyα forest is performed. This problem is approached by utilising the Lyα forest transmitted flux power spectrum at z∼5. The integrated heating during reionsation has a measurable impact on the power spectrum. The integrated heating is parameterised using the cumulative energy per proton deposited into a gas parcel at the mean background density. A Markov Chain Monte Carlo approach is used to recover the cumulative energy per proton with a statistical uncertainty of ∼ 20 per cent (at 68 per cent confidence interval), by making assumptions consistent with current observational data sets. However, systematics may increase the uncertainty to ∼ 30 per cent at these redshifts. This method can distinguish between early (z = 12) and late (z= 7) reionisation in the simulations. Finally, to expand on this investigation, the first constraints on the cumulative energy per proton using recent Lyα flux power spectrum measurements at high redshift are obtained. A consistent picture of galaxy driven reionsation with reionsation occurring at z∼9 is found.